Associations of physical activity with academic achievement and academic burden in Chinese children and adolescents: do gender and school grade matter? - Danqing Zhang; Jintao Hong; Sitong Chen; Yang Liu (BMC, 2022)
Abstract Background Physical activity (PA) was significantly associated with cognition and mental health in children and adolescent. However, there were few studies examining the associations of PA with academic achievement (AA) and academic burden (AB) by gender and school grade. Hence, this study aimed to 1) investigate the associations of moderate-to-vigorous PA (MVPA) with AA and AB in Chinese children and adolescents, and 2) assess whether these associations vary by gender and school grade. Methods Using a multi-stage stratified cluster sampling design (at four different regions in Southern east China), 2653 children and adolescents (8-19 years old, 51.2% girls) were included. A self-reported questionnaire was used to collect data on study participants' gender, school grade, family social economic status (SES), parental education level, MVPA, AA and AB. Binary logistic regression was applied to examine the associations of MVPA with AA (groups: above-average AA, average and below-average AA) and AB (groups: reporting AB, reporting no AB) with odds ratios (ORs) and 95% confidence intervals (CIs). After testing gender*grade interaction, those associations were explored by gender and school grade separately. Results In the overall sample, compared with children and adolescents who did not meet the PA guidelines (at least 60 min MVPA daily), children and adolescents who met the PA guidelines were more likely to have above-average (OR = 1.61, 95% CI: 1.21-2.11) AA, and report no AB (OR = 1.61, 95% CI: 1.13-2.30). In both genders, meeting the PA guidelines was positively associated with above-average AA (OR = 1.43, 95% CI: 1.01-2.03 for boys; OR = 2.22, 95% CI: 1.43-3.44 for girls). However, the significant relationship between meeting the PA guidelines and AB was observed only in girls (OR = 1.99, 95% CI: 1.17-3.39). Meeting the PA guidelines was positively associated with above-average AA (OR = 1.68, 95% CI: 1.18-2.40), and reporting no AB (OR = 1.77, 95% CI: 1.08-2.91) only in middle school students. Conclusions This study suggested that sufficient PA may be a contributary factor of improved AA and lower level of AB in Chinese children and adolescents. However, associations of PA with AA and AB may be different across gender or school grade. Promoting PA among girls or middle school students may be a good approach to improve AA and reduce AB.